146k views
0 votes
Whats x^2-2x-2










akjdcpiwhbfcnkluje

User Santh
by
5.0k points

2 Answers

2 votes

Answer:

Explanation:

1 In general, given a{x}^{2}+bx+cax

​2

​​ +bx+c, the factored form is:

a(x-\frac{-b+\sqrt{{b}^{2}-4ac}}{2a})(x-\frac{-b-\sqrt{{b}^{2}-4ac}}{2a

​2a

​−b+√

​b

​2

​​ −4ac

​​

​​ )(x−

​2a

​−b−√

​b

​2

​​ −4ac

​​

​​ )

2 In this case, a=1a=1, b=-2b=−2 and c=-2c=−2.

(x-\frac{2+\sqrt{{(-2)}^{2}-4\times -2}}{2})(x-\frac{2-\sqrt{{(-2)}^{2}-4\times -2}}{2})(x−

​2

​2+√

​(−2)

​2

​​ −4×−2

​​

​​ )(x−

​2

​2−√

​(−2)

​2

​​ −4×−2

​​

​​ )

3 Simplify.

(x-\frac{2+2\sqrt{3}}{2})(x-\frac{2-2\sqrt{3}}{2})(x−

​2

​2+2√

​3

​​

​​ )(x−

​2

​2−2√

​3

​​

​​ )

4 Factor out the common term 22.

(x-\frac{2(1+\sqrt{3})}{2})(x-\frac{2-2\sqrt{3}}{2})(x−

​2

​2(1+√

​3

​​ )

​​ )(x−

​2

​2−2√

​3

​​

​​ )

5 Cancel 22.

(x-(1+\sqrt{3}))(x-\frac{2-2\sqrt{3}}{2})(x−(1+√

​3

​​ ))(x−

​2

​2−2√

​3

​​

​​ )

6 Simplify brackets.

(x-1-\sqrt{3})(x-\frac{2-2\sqrt{3}}{2})(x−1−√

​3

​​ )(x−

​2

​2−2√

​3

​​

​​ )

7 Factor out the common term 22.

(x-1-\sqrt{3})(x-\frac{2(1-\sqrt{3})}{2})(x−1−√

​3

​​ )(x−

​2

​2(1−√

​3

​​ )

​​ )

8 Cancel 22.

(x-1-\sqrt{3})(x-(1-\sqrt{3}))(x−1−√

​3

​​ )(x−(1−√

​3

​​ ))

9 Simplify brackets.

(x-1-\sqrt{3})(x-1+\sqrt{3})(x−1−√

​3

​​ )(x−1+√

​3

​​ )

User Fredpi
by
4.9k points
4 votes

Answer:

x = 1±sqrt(3)

Explanation:

x^2-2x-2=0

This polynomial does not factor, so we can use completing the square to solve.

Add 2 to each side

x^2-2x-2+2 =2

x^2 -2x =2

b=-2

We take b/2 and then square it

-2/2 = -1 then square it (-1)^2 =1

Add 1 to each side

x^2 -2x +1 =2+1

The left side is equal to (x+ (b/2) )^2

(x-1) ^2 = 3

Take the square root of each side

sqrt(x-1)^2 = ±sqrt(3)

x-1 = ±sqrt(3)

Add 1 to each side

x-1+1 = 1±sqrt(3)

x = 1±sqrt(3)

User Zed Blackbeard
by
4.9k points